Study of irradiation-induced vacancy-type defects in tungsten using positron annihilation spectroscopy - Renjith Ramachandran; S. Balaji (Nuclear Materials and Energy, 2023)
Tungsten has been considered as a potential candidate material for the application of plasma-facing components in magnetic confinement fusion reactors. Fusion neutrons introduce severe displacement damage into the first-wall materials along with a high amount of helium which is detrimental to the desirable material properties. Ion beam implantation combined with positron annihilation spectroscopy is a well-adopted method to investigate the irradiation damage in materials without any induced radioactivity. In this study, two separate tungsten samples were individually irradiated with 9.1 MeV Au5+ ions to a dose of 2.5 × 1014 ions/cm2 and 130 keV He ions to a dose of 1 × 1016 ions/cm2 with the intention to investigate the evolution of vacancy-type defects in the absence and presence of helium. The irradiated samples were subjected to isochronal annealing and characterized using positron annihilation Doppler broadening spectroscopy. The evolution of vacancy-type defects during different stages of annealing was investigated using defect-sensitive positron S-parameter. An increase in S-parameter due to the presence of vacancy-type defects was observed upon irradiation in both samples. The S-parameter variations with respect to the temperature showed different stages of vacancy annealing corresponding to stage III from 473 K to 673 K where the migration and clustering of mono-vacancies occurs, stage IV from 673 K to 973 K due to the growth of nano-voids and stage V from 973 K to 1273 K due to the dissociation of nano-voids. Complete recovery of irradiation-induced defects occurred in both samples at 1273 K. Both the samples showed similar vacancy annealing stages and no signature on the formation and growth of He-vacancy clusters or He bubbles was observed in the present study.